PENGARUH PEMBERIAN AKUPRESURE DAN AROMATERAPI LAVENDER TERHADAP KUALITAS TIDUR PADA PERIMENOPAUSE - Sartika, Dewi; Fahnawal, T. Marzila; Ribut Sulistyawati, Tri (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
Perimenopause is a phase of menopause change that occurs several years before menopause, which includes changes from the ovulation cycle to the anoovulation cycle with signs of menstrual cycle irregularities. The World Health Organization (WHO) shows an increase in the number of women entering the climacterium phase, which is estimated to increase to more than one billion by 2030. Perimenopausal women often experience sleep disorders or insomnia because serotonin levels decrease so that the amount of estrogen decreases. Insomnia can be treated using acupressure massage and lavender aromatherapy. The purpose of the study was to determine the effect of acupressure and lavender aroma therapy on perimenopausal insomnia. The design in this study is pre-experimental with one group pretest and posttest design. The sampling technique in this study uses purposive sampling. The results of the study showed that there was an effect of acupressure and lavender aromatherapy on perimenopausal women, as evidenced by the results of a statistical test with a value of p 0.000 (p < 0.05) in the 2024 Karimun Health Center Work Area. The suggestion of the results of the study is expected to improve the ability in non-pharmacological therapy, namely the influence of acupressure and aroma lavender therapy to reduce insomnia in perimenopause among the community.